Chemokine CCL2 and its receptor CCR2 in different age groups of patients with COVID-19 - Vahid Bagheri; Hossein Khorramdelazad; Mehdi Kafi; Mitra Abbasifard (BMC Immunology)
Abstract Background Despite the development of various antiviral drugs, most of them are not effective in the treatment of coronavirus disease 2019 (COVID-19) as a hyperinflammatory disorder. Chemokine (C-C motif) ligand 2 (CCL2) is one of the critical CC chemokines involved in the pathogenesis and severity of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. This study aimed to investigate the expression of CCL2 and CC chemokine receptor 2 (CCR2) in COVID-19 patients. Methods Peripheral blood samples were collected from 60 confirmed COVID-19 patients and 60 age-matched healthy subjects. The ages of the subjects were categorized as follows: up to 20 years, 20 to 40 years, 40 to 60 years, and more than 60 years. CCL2 serum levels were measured using the enzyme-linked immunosorbent assay (ELISA). CCR2 gene expression in peripheral blood mononuclear cells (PBMCs) was measured employing real-time polymerase chain reaction (PCR). Results In all age groups, CCL2 serum levels were significantly elevated in patients compared to healthy controls (P < 0.0001). CCL2 levels were higher in severe patients than in moderate patients. Moreover, CCR2 expression by PBMCs was higher in patients compared to control subjects. However, a significant difference between patients and controls over 60 years of age was identified (P = 0.0353). There was no significant difference in CCR2 expression between moderate and severe COVID-19 patients. Conclusions Taken together, the findings demonstrate that CCL2 and CCR2 are upregulated in COVID-19 patients at protein and mRNA levels, respectively. Therefore, the CCL2/CCR2 axis may be a potential therapeutic target in order to improve patient outcomes.